Obtenção da fração proteica dioscorina de inhame (Dioscorea cayennensis): caracterização bioquímica e atividades biológicas - Sousa, Aleson Pereira de (2017)
Seeds, rhizomes and tubers are welcomed with sources of bioactive molecules, which are related to health promotion, such as proteins and other components of plant sources. (Dioscorea cayennensis) is part of the Brazilian food habit, it is necessary to study the proteins present in this plant. The objective of this work was to isolate and characterize biochemically the dioscorin proteic fraction (DPF) present in the tubers of D. cayennensis, characterizing the presence of antinutritional compounds and antioxidant, antibacterial and antifungal biological activities. Isolation of DPF was performed with protein extraction in Tris-HCl 0.05M pH 8.3, followed by precipitation in Ammonium Sulfate (F45-75). The molecular weight of DPF was determined by SDS-PAGE and MALDI-ToF, characterized by the presence of a major component with a mass of approximately 28 kDa corresponding to dioscorin. When tested for the presence of phytochemicals and antinutritional compounds (lectins and trypsin inhibitors), the presence of these compounds was not detected in the DPF. The amino acid composition of the fraction was determined and the antioxidant activity estimated by the ABTS and DPPH methods. Glutamic acid, Aspartic acid and Arginine were the amino acids that showed higher levels in DPF, which explains the antioxidant activity, suggesting that the interaction of these amino acids seems to act on reactive molecules making them stable. Finally, in the evaluation of the antibacterial and antifungal activity of the total extract and DPF against different strains of microorganisms, an antibacterial potential was detected between 50-500 μg/mL of protein for inhibition of the growth of strain of L. monocytogenes.